New Possibility for REE Determination in Oil. (15th May 2012) - Soin, Alexander; Maryutina, Tatiana; Musina, Natalya; Soin, Andrey
Abstract : A novel approach of rare earth elements (REE) determination in crude oil is suggested. Special application of countercurrent chromatography (CCC) is used as a sample pretreatment tool. An oil sample is continuously pumped through the rotating coil column (RCC) as a mobile phase, while an aqueous phase (nitric acid solution) is retained as a stationary phase. Two phases are kept well mixed and agitated, but there is no emulsion at the interface under the chosen conditions. Special features of CCC give an opportunity to vary the volume of oil samples to be analyzed from 10 mL to 1 L or more. Trace metals are preconcentrated into 10 mL of stationary phase (acidic solutions) pumped out of the column so that analysis can be easily determined with inductively coupled plasma mass spectrometry (ICP-MS) without additional sample preparation procedures. Optimal concentration of nitric acid in the stationary phase for preconcentration of REE from oil by CCC has been investigated. The combination of CCC with ICP-MS gives the possibility to develop a rapid, reliable, and accurate method of trace metal including rare earth elements (REE) determination in crude oils and oil products. Such method could be an alternative for unexpanded and expensive neutron-activation analysis (NAA).